Peningkatan Strategi Pembelajaran Seni Musik untuk Meningkatkan Prestasi Belajar Pada Siswa Kelas IX.10 di SMP Negeri 13 Pekanbaru - Marjeni Maisasna (Instructional Development Journal, 2018)
Based on the results of the research that has been obtained about the strategy of learning music art to improve student achievement in SMP Negeri 13 Pekanabaru, some conclusions can be drawn such as the following: Learning preparation strategies. The main step shown by the teacher with the preparation of lesson plans that is oriented towards the curriculum and syllabus used. The RPP lists the strategies and methods of learning that are applied. Management strategies in each class. Teachers teach with different methods for each class because each class has different characters. Strategy for using learning media. The teacher leads to preparation and utilizing media and learning tools that are in accordance with the material and facilities available in the school's music lab. Strategy approach to motivate students. To motivate students, the teacher takes a personal, group and functional approach. The strategy of motivational approaches by teachers is supported by school participation by providing a means of supporting good learning. Strategy for evaluation and value taking. In this strategy the teacher holds a score not only in the UTS and UAS, but by holding a daily test after the completion of Basic Competence. The teacher also conducts assessments at any time in the learning process takes place by looking at the students' responses, seeing the answers to oral questions from the teacher. The results of the evaluation will be followed up by the teacher as the stage of learning learning. Strategies for developing students' musical art learning experiences. In this strategy the teacher develops student learning activities, by increasing the learning activities of music practice compared to learning music theory, but by not putting aside the theory that remains present throughout the course of learning. In addition, there are also many activities or activities supporting the achievement of students' musical arts achievements at school.